Dalit Women in Cinema: A Narrative of Gender and Caste. Issue 1 (10th March 2022) - Lalitha, S.; Pankaj, Ajeet Kumar
Abstract: Dalit women in India experience gender in an entirely different way from upper‐caste women because, along with gender discrimination, Dalit women face caste discrimination. Their experience of gender discrimination intersects with their caste identity, which intensifies their suffering. Dalit women experience gender‐based discrimination and social exclusion and stigma. Drawing from the Tamil movie Karnan, two Bollywood movies— 200‐Halla Ho and Article15 —and the Netflix web series Azib Dastan ‐ Geeli Pucchi (an anthology), we endeavor to answer several questions: What patterns exist in the gender‐ and caste‐based humiliation of Dalit women? How do gender and caste intersect in the humiliation and social exclusion of those women? How is their experience of gender‐based discrimination different from that of upper‐caste women? How do Dalit women assert their agency and struggle against gender and caste oppression in society? What kind of resilience do they rely upon to negotiate gender and caste discrimination? What inspires and motivates them to fight for their dignity? Despite the challenges and hurdles, how are these women achieving their aspirations?